MANASA BHAVA IN THE ETIOPATHOGENESIS OF ANIDRA IN CONTEXT OF INSOMNIA - Khare Kumudini Mala; Khare Manish; Kande Aradhana (International Journal of Applied Ayurved Research, 2017)
Life is the complex union of Satva, Atma and Sharira. Thus, mind, body and soul influence each other. When the mind and indriyas get exhausted, they withdraw themselves from their objects and the individual sleeps The production of Anidra is considered to be by the impairment of general mental functions, the presence of alpa Satva, vitiation of both sharirika (vata, pitta and kapha) and manasa dosha (rajo and tama) and also by vitiation of manovaha srotasa. Vitiated vata hampers the happiness of Manas and provokes bhaya, shoka, moha, dinta etc. These Mansika bhavas play vital role in the etiopathogenesis and exacerbation of the disease. Manas play an important role in the loss of sleep The heart communicates with the brain and the rest of the body in following ways i.e. neurologically, biochemically, biophysically and energetically.